Foreign Policy of Nepal: Continuity and Changes - Khanal, Gopal (Journal of APF Command and Staff College, 2019)
After the unification of Nepal, the founder of the nation, King Prithvi Narayan Shah formulated an underlying principle of Nepal's foreign policy based on Geopolitics. He described the geographical situation of Nepal as a ‘yam between two boulders’, referring to the two big neighbours of Nepal – China and India. King Prithvi Narayan Shah was not only a great warrior but a visionary leader, who had appropriately assessed the geopolitical sensitivities of Nepal and adopted non-aligned foreign policy. He also said it was important for the county to keep a balanced relationship with these two huge neighbours. He cautiously moved maintained distance and balance considering the imperatives of the fragile situation. Nepal's foreign policy thereafter has passed through the turbulent periods; extreme loyalty had been maintained to the southern neighbour and pro-northern approach surfaced consequently. With the formation of the elected government after the promulgation of new constitution, major shift is observed in Nepal's foreign policy- the diversification of Nepal's trade and transit to China.